HOW SOCIAL MEDIA MARKETING STRATEGIES AFFECT CUSTOMER BEHAVIOR IN THE FOOTBALL BROADCASTING INDUSTRY - Rachmadeputra, Reyhan
Indonesia is a country that has been known as a big fan of football. Football has been an entertainment for many Indonesian people for a long time. In broadcasting football matches, a company should have/obtain a broadcasting rights from the concerned parties. The price for a broadcasting rights varied from one league/competition to others. Over the years, several companies has took turns in obtaining the broadcasting rights of many top European leagues in order to be able to broadcast it in Indonesia. Starting from 2019, a company called Mola TV took turn as the holder of the broadcasting rights of some top European football leagues. Mola TV is a multi-platform service that provides video on demand with over-the-top services in South East Asian countries including Indonesia. Mola TV has obtained some of the broadcasting rights of the top European Football leagues, however this is their last year as the company who held the broadcasting rights for one of the top leagues in Europe, the English Premier League as their contract ran out this year. However, even though there is a company that provides this service, there are some people in Indonesia who watch football matches from illegal broadcasters. Although it is free, there are some risks that is dangerous for people who watches football matches from illegal broadcasters. Illegal broadcasters can be found in the internet and the social media such as Twitter. There are many sources/links that can be found if people searches for a certain keywords. In this research, the researcher aims to understand and pay attention to the factors that make people consume content from illegal broadcasters and also find marketing strategies that can influence the behavior of the audience since many Indonesian audiences choose to watch football matches from illegal broadcasters on Twitter or illegal websites. This research is done qualitatively by the researcher. The researcher collects the data by conducting an in depth semi structured interview to 15 key informants. The key informants are Indonesian audiences who are above 18 years old, watch football weekly, know/subscribes to Mola TV, and were aware of the existence of the illegal broadcaster. In the interview, the key informants were asked about their reason for watching football matches from illegal broadcasters and what kind of social media marketing strategies/contents that may make them change their behavior. Then, the researcher uses Thematic analysis to analyze the data that is collected from the interview. Besides that, the researcher also compares the data collected from the key informants with the strategy that Mola TV has implement in their social media, in this case, Instagram with the aim of finding a gap between these two. The result is that the key informants’ reason for watching football matches from illegal broadcasters are affected by some factors. It includes factors such as their financial condition/situation, habit, perception, and environment. Moreover, they need Mola TV to post more interesting content, campaign, collaborate with Key Opinion Leader (KOL)/influencers, etc in their social media account.